Continuous Production of Squalane Using 3D Printed Catalytic Supports. Issue 3 (1st July 2019) - García, Sonia; Poulston, Stephen; Modeshia, Deena; Stavarek, Petr; Ujcic, Massimo; Lali, Farzad; Alves, Manuel A.; Araújo, José D.; Krusche, Michael; Ullrich, Frank; Maier, Diana
Squalene (SQE) was fully converted into squalane (SQA) in a continuous reactor. The design of a three-dimensional (3D) printed support allowed selectivity to be tuned towards squalane. The advantages of being able to design the geometry of the catalytic support using 3D printing technology are presented in this paper.